Effects of tea polyphenols on anti-inflammation and promotion of wound healing and its mechanisms - ZHAO Hangye; XIA Chen; HE Puming; TU Youying (浙江大学学报. 农业与生命科学版)
This study focuses on the effects of tea polyphenols (TPPs) on anti-inflammation and promoting wound healing in vivo and its mechanisms. ICR mice were selected as animal materials to make the wound. The wounded mice were treated with 0.3%, 0.5%, 0.8% and 1.0% TPPs, respectively. The treatment with artificial cell healing membrane was used as the positive control, and the blank control was set up. The effects of different concentrations of TPPs on the immune system and granulation tissue of wounded mice were measured after 9 d. The results showed that 0.5% TPPs could accelerate the wounded mice healing and the healing speed of this treatment was faster than the positive control. Meanwhile, 0.3% and 0.5% TPPs treatment groups could reduce the concentrations of tumor necrosis factor-α (TNF-α) and interleukin-2 (IL-2) in the late stage of wound healing to prevent excessive inflammatory reaction. Superoxide dismutase (SOD) activity in wound tissues was decreased significantly by the TPPs treatment as compared with the blank control group, which showed that TPPs may help to eliminate excessive free radicals in wound, and then to prevent its damage to the body. Hematoxylin-eosin (HE) staining sections of granulation tissue at the wound showed that TPPs treatment could promote the formation of capillaries in the wound. The function of TPPs in promoting wound healing was related to its concentration. At lower concentrations (below 0.5%), with the increase of concentration of TPPs, the ability of promoting wound healing increased; at higher concentrations (above 0.8%), TPPs showed the physiological characteristics of inhibiting wound healing. To some extent, the experimental results elucidate the partial mechanisms of promoting wound healing and anti-inflammation by TPPs and find that the suitable concentration range of TPPs for promoting wound healing is 0.3%-0.8%.